1991
DOI: 10.1136/hrt.66.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypothermia in the management of resistant automatic tachycardias in children.

Abstract: Background-Automatic focus tachy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 11 publications
0
28
0
1
Order By: Relevance
“…Others have found that hypothermia may slow the automaticity of cardiac pacemaker cells, resulting in slower HRs and improved hemodynamics in some patients with automatic tachycardias. 7 These studies suggest electrophysiological mechanisms by which there was less refibrillation in our hypothermic animals.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Others have found that hypothermia may slow the automaticity of cardiac pacemaker cells, resulting in slower HRs and improved hemodynamics in some patients with automatic tachycardias. 7 These studies suggest electrophysiological mechanisms by which there was less refibrillation in our hypothermic animals.…”
Section: Discussionmentioning
confidence: 88%
“…[1][2][3] Animal studies in which brain injury models were used have demonstrated decreased ischemic cellular injury, decreased brain infarct size, and improved functional status from neurological damage in those animals receiving hypothermic treatment; clinical studies have shown that this is feasible and safe. [2][3][4][5][6] Induced hypothermia has also been advocated for various cardiac conditions, including treatment of refractory arrhythmias 7 and attempts to decrease myocardial infarct size in patients undergoing primary angioplasty for acute myocardial infarction. 8 Induced hypothermia during cardiac surgery has been used successfully to protect the brain from global ischemia since the 1950s.…”
mentioning
confidence: 99%
“…Profound hypothermia with circulatory arrest is increasingly used as an adjunct to non-cardiac surgical procedures to facilitate operative exposure and repair (Swain et al 1990). Hypothermia reduces the automaticity of cardiac pacemaker cells and is therefore valuable in the treatment of tachycardia in children (Balaji et al 1991). Bailes et al (1991) have demonstrated the possibility of achieving successfully complete exsanguination, blood substitution and ultra-profound body temperature, while continuous circulation of the blood substitute is maintained.…”
Section: Introductionmentioning
confidence: 98%
“…Blood pH during hypothermia profoundly affects the heart (McConnell et al 1975;Swain et al 1984) and other organs (Norwood et al 1979). Hypothermia is known to reduce cardiac output (Wilford et al 1986) and increase systemic vascular resistance (Balaji et al 1991;Swain et al 1990). The oxygen demand is also reduced such that the oxygen supply balance is unaffected, provided the shivering response to hypothermia has been abolished by the use of paralysis and artificial ventilation (Balaji et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive care characteristically includes surface cooling, atrial pacing, and antiarrhythmic rate-control therapy (3,6). Although catecholamines may worsen the tachyarrhythmia, such inotropes are commonly used to support the circulation.…”
Section: Introductionmentioning
confidence: 99%